EDUKASI KESEHATAN DAN PEMERIKSAAN GOLONGAN DARAH PADA MURID SD NEGERI 13 DI DESA TUNGKAL SELATAN KECAMATAN PARIAMAN UTARA - Yustini Alioes; Husnil Kadri; Eti Yerizel; Hirowati Ali; Rauza Sukma Rita; Desy Arisanti (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
Elementary school students are consumers who are among those who consume the most food and beverages. Food and drinks sold around the school contain many hazardous substances such as dyes that have been banned from circulating (Rhodamine B in iced drinks, jelly drinks, and so on) and other additives such as formalin which is used as a chewy substance in meatballs sold in carts and restaurants that can cause acute poisonings such as allergies, coughs and chronic poisonings such as cancer of the liver, kidneys and other organs. The purpose of this activity is to increase knowledge about substances in food and an introduction to blood group examination. This activity was carried out at SD Negeri 13 Tungkal Selatan Village in North Pariaman District. The method of activity is in the form of counseling and demonstration. According to the survey before the blood group examination, it turned out that most of the elementary school students did not know their blood type. Before the blood group examination, the students were also given knowledge about determining a person's blood type. After this counseling was carried out, respondents became more aware of the impact of food/snacks on health, and respondents knew their respective blood types. Of the 64 students, there are 22 A, 17 B, 12 AB, 13 O. To avoid problems related to food and blood type. There is a need for continuous health education for elementary school students.